Cosmic Miniatures and the Future Sense : Alexander Kluge's 21st-Century Literary Experiments in German Culture and Narrative Form. - Adelson, Leslie A. (Interdisciplinary German cultural studies., 2017)
The series publishes monographs and edited volumes that showcase significant scholarly work at the various intersections that currently motivate interdisciplinary inquiry in German cultural studies. Topics span all periods of German and German-speaking lands and cultures from the local to the global, with a special focus on demonstrating how various disciplines - history, musicology, art history, anthropology, religious studies, media studies, political theory, literary and cultural studies, among others - and new theoretical and methodological paradigms work across disciplinary boundaries to.